2016 APWG Symposium on Electronic Crime Research (eCrime) 2016
DOI: 10.1109/ecrime.2016.7487948
|View full text |Cite
|
Sign up to set email alerts
|

When cybercrimes strike undergraduates

Abstract: Cybercrimes can cause various kinds of harm to those affected. This paper focuses on how cybercrimes impact undergraduate students, a group particularly vulnerable to cybercrimes due to their extensive use of technology and their recently gained financial responsibility and social independence. We present a mixed methods study to understand students' knowledge, perceptions, and behaviors regarding cybercrimes. 10 semi-structured interviews provided the groundwork for a theoretical model, which was subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…For example, it has been noted that such a population represents a group that is most at risk of being victims of cybercrime. 41 Further research is warranted to explore how the results reported in this study compare to a sample from a wider and more varied population.…”
Section: Discussionmentioning
confidence: 94%
“…For example, it has been noted that such a population represents a group that is most at risk of being victims of cybercrime. 41 Further research is warranted to explore how the results reported in this study compare to a sample from a wider and more varied population.…”
Section: Discussionmentioning
confidence: 94%
“…Younger adults often display substantial confidence in their ability to comprehend and control privacy settings on social media [4]. However, the spotlight should shine brightly on older adults, who bring a diverse range of knowledge to this domain.…”
Section: Perceptions and Approaches To Digital Privacy (Rq1)mentioning
confidence: 99%
“…As there have been varied findings in this area, further research is suggested to explore potential differences in gender and ISA. In previous research, it has been suggested that younger populations are more frequently engaged in the use of digital technology, therefore increasing their potential susceptibility to cybercrime 28 . Aspects of impulse control have also been linked to risky online behaviours, which it turn could been linked to the age-related differences in ISA observed here [29][30][31] .…”
Section: Fomo and Isamentioning
confidence: 99%